Gender and migration - Sarkin, Jeremy Julian (2024)
Gender-based violence (GBV) is widespread globally and is based on social roles. These social roles represent society’s expectations of men and women carrying out stereotyped functions and behaviours. These gendered social expectations vary across culture, space and time. Drawing from an empirical study in Israel and building on the previous literature on these issues, this qualitative and interdisciplinary article identifies various forms of GBV along Eritrean women’s journey from their home country into Israel. The empirical work helps to examine the findings of previous theoretical studies. This article establishes that there is a continuum of violence for women, especially refugees and asylum seekers, rooted in the standard system of oppression – patriarchy. This has triggered the flight and trafficking of refugees from Eritrea through the Sinai Desert and into Israel. The article argues that structural and cultural violence emanating from both the hosted community and the host community play significant roles in allowing the circumstances for GBV to thrive throughout the entire refugee cycle. What can be seen is the creation of multiple layers of vulnerabilities, particularly the specific social–legal–economic marginalization of segments of the population, including Eritrean asylum-seeking women. Reacting to this continuum of violence, many participants in the study argued that it was necessary to adopt strategies to create a continuum of resilience and resistance grounded on women’s sorority, support and agency.